2022
DOI: 10.1002/er.7938
|View full text |Cite
|
Sign up to set email alerts
|

Rh (0) nanoparticles impregnated on two‐dimensional transition metal carbides, MXene , as an effective nanocatalyst for ammonia‐borane hydrolysis

Abstract: Summary MXene, which are known as two‐dimensional transition metal carbides have received heavy interest due to their rich elemental diversity and many fascinating physical and chemical properties. Here, Rh (0) nanoparticles deposited MXene catalysts were synthesized by an easy wet‐impregnation method for hydrogen production. Rh (0) nanoparticles were conveniently loaded on the surface of MXene (Rh/MXene) were used as an effective nanocatalyst for the hydrogen production from the hydrolysis of ammonia‐borane (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…In recent years, MXenes, the newly emerged two-dimensional (2D) transition metal carbide and nitride, were first discovered by Gogotsi in 2011. The general formula for MXenes is M n +1 X n T x ( n = 1–3), where M is for the transition metal, X represents the symbol for the element C or N, and T x stands for the surface functional group (−OH, −O and −F) . MXenes have attracted considerable attention in the EMW absorption field owing to their large specific surface area, unique layered structure, and metallic conductivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, MXenes, the newly emerged two-dimensional (2D) transition metal carbide and nitride, were first discovered by Gogotsi in 2011. The general formula for MXenes is M n +1 X n T x ( n = 1–3), where M is for the transition metal, X represents the symbol for the element C or N, and T x stands for the surface functional group (−OH, −O and −F) . MXenes have attracted considerable attention in the EMW absorption field owing to their large specific surface area, unique layered structure, and metallic conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…The general formula for MXenes is M n+1 X n T x (n = 1−3), where M is for the transition metal, X represents the symbol for the element C or N, and T x stands for the surface functional group (−OH, −O and −F). 5 MXenes have attracted considerable attention in the EMW absorption field owing to their large specific surface area, unique layered structure, and metallic conductivity. Particularly, the abundant surface terminations originating from HF etching can offer additional polarization relaxation and EMW scattering.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen energy is one kind of new energy promoted by various countries at present. Compared with traditional energy, hydrogen energy has the advantages of very high energy value, wide application range, and clean and pollution-free [1][2][3]. Hence, interest in developing suitable hydrogen storage materials has grown rapidly over the past few decades.…”
Section: Introductionmentioning
confidence: 99%
“…Konus et al prepared TiO 2 ‐supported Ru (0) nanoparticles by in situ reduction process and performed hydrogen production from the AB hydrolysis with a TOF value of 200 min −1 at room temperature 14 . Karatas et al developed Rh (0) nanoparticles on MXene and the catalysts show significant catalytic performance in the hydrogen production with 288.4 min −1 TOF value at room temperature 15 . Karatas et al reported first time, the ternary NiRuPt alloys on SiO 2 and investigated the catalytic performance of hydrogen production using decomposition of hydrazine in an alkaline medium.…”
Section: Introductionmentioning
confidence: 99%
“…14 Karatas et al developed Rh (0) nanoparticles on MXene and the catalysts show significant catalytic performance in the hydrogen production with 288.4 min À1 TOF value at room temperature. 15 Karatas et al reported first time, the ternary NiRuPt alloys on SiO 2 and investigated the catalytic performance of hydrogen production using decomposition of hydrazine in an alkaline medium. The catalytic performance of ternary alloys was 324.1 min À1 for hydrazine decomposition.…”
Section: Introductionmentioning
confidence: 99%